Genome Mining of the Lipopeptide Biosynthesis of Paenibacillus polymyxa E681 in Combination with Mass Spectrometry: Discovery of the Lipoheptapeptide Paenilipoheptin. (23rd February 2018) - Vater, Joachim; Herfort, Stefanie; Doellinger, Joerg; Weydmann, Max; Borriss, Rainer; Lasch, Peter
Abstract: Paenibacillus polymyxa strains are qualified for agro‐biotechnological uses such as plant growth promotion and for biocontrol strategies against deleterious phytopathogenic competitors in the soil depending on their attractive arsenal of bioactive compounds. Moreover, they are potent producers of antibiotics for medical applications. To identify new products of such organisms, genome mining strategies in combination with mass spectrometry are the methods of choice. Herein, we performed such studies with the Paenibacillus strain E681. Bioinformatic evaluation of its genome sequence revealed four gene clusters A–D encoding nonribosomal peptide synthetases (NRPSs). Accordingly, four lipopeptide families were detected by matrix‐assisted laser desorption/ionization time‐of‐flight mass spectrometry (MALDI‐TOF MS). Clusters A and D codify the well known fusaricidins and polymyxins. A yet‐unknown lipoheptapeptide was discovered and structurally characterized by de novo sequencing by using MALDI‐LIFT‐TOF/TOF MS. It was designated as paenilipoheptin. From structure predictions we infer that the production of this agent is encoded by gene cluster C. Gene cluster B encodes the synthesis of tridecaptins, a family of open‐chain lipotridecapeptides. Strain E681 produces new subspecies of such compounds (tridecaptins E) showing variations both in their fatty‐acid part as well as in their peptide part. Abstract : With a little pep : The organization of the phn gene cluster coding for the biosynthesis of lipopeptides is analyzed, leading to the discovery of novel lipoheptapeptides, named paenilipoheptins. Detected and characterized by MS, they are found to be cyclic compounds that contain a C12–13 β‐amino fatty acid that is integrated into the peptide ring.